Risk factors of recurrent periprosthetic joint infection of the knee after two-stage reimplantation - Do Weon Lee; Hyuk-Soo Han; Du Hyun Ro (Knee Surgery & Related Research)
Abstract Introduction Prosthetic joint infection (PJI) is one of the most common and detrimental complications of total knee replacement arthroplasty (TKA). Despite extensive efforts, including two-stage reimplantation, to eradicate PJI, it still recurs in a substantial number of patients. However, the risk factors of recurrence after two-stage reimplantation of the knee have not been established. In this study, it is hypothesized that there will be certain risk factors of recurrence after two-stage reimplantation for PJI of the knee. Materials and methods From March 2002 to December 2022, 65 knees that underwent two-stage reimplantation for PJIs in a single, tertiary hospital were retrospectively reviewed, and 44 patient-related, laboratory-related, and surgery-related factors, including body mass index, pathogen type, and the usage of transfusions, were selected as the potential risk factors for recurrence. Survival analysis using the Kaplan–Meier method and subsequent Cox proportional hazard regression were performed. Results Out of the 65 knees that underwent two-stage reimplantation, infection recurred in 15 knees (23.1%) in a median 11 (range 4–108) months. The Cox proportional hazards regression showed that infection of revision TKA, mixed pathogen-type infection, and higher serum erythrocyte sedimentation rate (ESR, mm/h) level increases the risk of recurrence (p-values < 0.001, 0.04, and 0.009; hazard ratios 40.29, 1.53, and 1.03, respectively). Conclusions A significant portion of PJI of the knees recurred after two-stage reimplantation. Revision TKA at the time of initial PJI, mixed pathogen-type infection, and higher serum ESR level were three significant risk factors of PJI recurrence. Surgeons should be more cautious in suspecting PJI relapse for these specific occasions. Level of evidence III, retrospective cohort study.